Geographical Information System of Bus and Travel Counter in Padang City Using BFS Method Based on Mobile Web - Sularno, Sularno; Astri, Renita; Anggraini, Putri; Prima Mulya, Dio; Mulya, Dwiki (Universitas Negeri Semarang, 2021)
Purpose: One of the main objectives of the research is the BFS (Breadth-First Search) algorithm method in the search for nearby bus and travel counters using GPS found on each device used in the search process. Each smartphone produces a different coordinate point with an average distance difference of 30.2 meters to the hardware coordinate point. Each GPS embedded in the smartphone will process the data according to the location conditions of the user's point of existence. The methodology for system development is a standard process for a team of developers to connect all the steps needed in analyzing, designing, implementing, and maintaining information systems. Methods: The methodology becomes a guideline in system development activities in SDLC. The SDLC model used in this study is the WaterFall Model. Result: The results of this study are expected to facilitate the public in booking tickets and to find the nearest location from the bus and travel counters. Novelty: The novelty of this research is the development of GIS as a search for the location of bus and travel counters using the breadth-first search algorithm. This research can help the community find the location of the nearest bus and tourist counter in the city of Padang.